Leontyne Price, opera superstar - Williams, Sylvia B. (Picture-story biographies., 1984)
A brief biography of the black opera singer who is one of the most celebrated sopranos of her time and who, among other honors, opened the inaugural season of the new Metropolitan Opera House.